Disease management in Hawkes Bay apple orchards converting to organic production - Tate, K.G.; Manktelow, D.W.; Walker, J.T.; Stiefel, H. (New Zealand Plant Protection, 2000)
Disease control achieved by 10 apple growers converting to organics during the 199798 and 199899 seasons is reported Two orchards experienced black spot outbreaks each season while the remainder averaged 05 spotted fruit Powdery mildew was severe in 199798 but acceptable in 199899 Fruit rots after coolstorage averaged 011 for different varieties in 199798 and 030 in 199899 Fungicide applications averaged 116 in 199798 and 184 in 199899 which was a net increase in chemical use Copper use was below 3 kg/ha/year The mostused spray programme was a greentip copper three prebloom limesulphurs sulphur/copper bloom sprays and sulphur or sulphur/ copper sprays thereafter Results showed that acceptable disease control is achievable in organic orchards but summer and core rots remain a concern